Different approaches to ergogenic, pre-, and probiotic supplementation in sports with different metabolism characteristics: A mini review - Wiacek, J.; Karolkiewicz, J. (Nutrients, 2023)
Sport disciplines with different metabolic characteristics require different dietary approaches. Bodybuilders or sprinters ("anaerobic" athletes) need a high-protein diet (HPD) in order to activate muscle protein synthesis after exercise-induced muscle damage and use nitric oxide enhancers (such as citrulline and nitrates) to increase vasodilatation, whereas endurance athletes, such as runners or cyclists ("aerobic" athletes), prefer a high-carbohydrate diet (HCHD), which aims to restore the intramuscular glycogen, and supplements containing buffering agents (such as sodium bicarbonate and beta-alanine). In both cases, nutrient absorption, neurotransmitter and immune cell production and muscle recovery depend on gut bacteria and their metabolites. However, there is still insufficient data on the impact of an HPD or HCHD in addition to supplements on "anaerobic" and "aerobic" athletes` gut microbiota and how this impact could be affected by nutritional interventions such as pre- and probiotic therapy. Additionally, little is known about the role of probiotics in the ergogenic effects of supplements. Based on the results of our previous research on an HPD in amateur bodybuilders and an HCHD in amateur cyclists, we reviewed human and animal studies on the effects of popular supplements on gut homeostasis and sport performance.